DINAMIKA DAKWAH DAN POLITIK DALAM PEMIKIRAN ISLAM MODERNIS DI INDONESIA - Abdur Razzaq (Wardah, 2014)
Da'wah and politics have a very big role in the repair process ummah. This study aims to analyze the history by using a comparative approach whose goal is to assess, examine and compare the leaders of Islamic modernist thinking about dakwah and political role in the process of repair people. Almost agreed that the process of repair people need the right method in dealing with the problems of Muslims is so complex. Syumuliah principle in Islam is not only at the level of concepts and doctrine alone, but also in the level of implementation of political and dakwah must be emphasis as community improvement efforts. The combination of theory Top-Down and Buttom-Up as one of the repair process is applied to the appropriate community improvement efforts and thorough. Top-Down Theory through political channels is implemented by setting up the system, improved legislation, thus leading to the making of policies that support the implementation of Islamic laws and facilitate the implementation of dakwah as people repair process. Implementation of the dakwah of significant improvement over the system either through parliament to fight for the implementation of Islamic law, while the theory Buttom-Up in the mission is the process of preparing the people to accept the system that has been fought through politics, the process of awareness, training, and raising awareness about the importance of returning to the teachings of Islam as perfect religion. Meeting of the implementation of these two theories would generate a society that is ready to implement Islam as rahmatan lil 'aalamin.